2010
DOI: 10.1007/s11422-010-9266-6
|View full text |Cite
|
Sign up to set email alerts
|

Sardonic science? The resistance to more humanistic forms of science education

Abstract: Resistance to more humanistic forms of science education is an endemic and persistent feature of university scientists as well as school science teachers. This article argues that science education researchers should pay more attention to its origins and to the subtleties of its stubborn influence. The paper explores some of the imperatives which dominate the continuing practices of teachers; the linkages between school and university science; and re-considers the relationships between learning science, learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Moreover, the pupils indicated that participation in these discussion lessons had helped them to see the relevance of science to their life (53.6% overall). These findings provide support for the claim that the inclusion of socio-scientific discussion within science education helps to promote both the learning of the basic science that impacts the issue under discussion, but also the pupils' development towards a functional scientific literacy (Aikenhead, 2006;Bryce, 2010;Bryce & Gray, 2004;Gray & Bryce, 2006;Sadler, 2004;Zeidler & Keefer, 2003). However, the data in Table 2 also show that for item J11, overall only 47.4% of pupils would like to discuss other topics, with females being more positive in this item than males (52.9% of females vs. 41.7% of males).…”
Section: Responses To Section J In the Pupil Questionnaire: The Globasupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, the pupils indicated that participation in these discussion lessons had helped them to see the relevance of science to their life (53.6% overall). These findings provide support for the claim that the inclusion of socio-scientific discussion within science education helps to promote both the learning of the basic science that impacts the issue under discussion, but also the pupils' development towards a functional scientific literacy (Aikenhead, 2006;Bryce, 2010;Bryce & Gray, 2004;Gray & Bryce, 2006;Sadler, 2004;Zeidler & Keefer, 2003). However, the data in Table 2 also show that for item J11, overall only 47.4% of pupils would like to discuss other topics, with females being more positive in this item than males (52.9% of females vs. 41.7% of males).…”
Section: Responses To Section J In the Pupil Questionnaire: The Globasupporting
confidence: 52%
“…However, traditionally the emphasis of Scottish science education is on preparing pupils for specialisation in the sciences. This has been described as the 'pipeline' (Aikenhead, 2006;Bryce, 2010;Kind & Taber, 2005), indicating that school science education currently functions as a filtering mechanism which feeds pupils through the system to become the next generation of scientists, clinicians and engineers.…”
Section: Introductionmentioning
confidence: 99%
“…They wrote: "an STSE orientation presents a particular image of science teaching and a particular set of pedagogical challenges that are different from 'normal' patterns of practice" (p. 955). Tom Bryce (2010) has in this journal discussed the resistance to humanistic science education in practice. He contrasted the dominant Science-for-scientists view (emphasising content) with Science-for-citizenship (emphasising contextual complexities).…”
Section: Effects On the Praxis Of Science Educationmentioning
confidence: 99%
“…Vision 2 is an outward looking view that links specifically to situations involving both science and social issues that are relevant to students' lives. Traditionally Vision 1 has been at the heart of most university science courses and much of school science, and to a large extent it remains so (Bryce, 2010;Miller et al, 2008;Osborne, 2010). As already mentioned, the notion of Vision 1 and Vision 2 was intended to be a heuristic rather than a pigeonholing device.…”
Section: Comparison Of the Lecturers' Accounts Of Sciencementioning
confidence: 99%